Islamic Agricultural Economic Financing Based On Zakat, Infaq, Alms And Waqf In Empowering The Farming Community - Muhammad Izzat Mohamed; Muhammad Hakimi Mohd. Shafiai (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2021)
In the development of the agricultural sector, farmers are the key to its success. However, to a certain extent, specific interventions need to be done considering the problems faced by most farmers, such as financial constraints, lack of assistance, facilities, agricultural tools, and lack of land, which are obstacles to developing farmers enterprises. Therefore, this study attempts to analyze the potential of Islamic social finance tools in farmers development, particularly in facilitating financial problems of farmers in line with the government efforts in strengthening the agricultural sector. The distribution of productive zakat, infaq, alms and waqf (ZISWAF), based on the application of contractual contracts inherent from Islamic legislation and the management of productive ZISWAF, will be highlighted in this paper. The methodology of this study is based on a qualitative approach like gathering information from library research, and hence it is analyzed based on a deductive approach. The management of ZISWAF is divided into two, namely consumptive and productive ZISWAF. Consumptive ZISWAF can assist farmers in meeting their daily needs. At the same time, productive ZISWAF can develop farmers agricultural enterprises through musaqah, muzaraah, mukharabah, and ijarah contracts. Accordingly, it can be argued that Islamic social finance can play a positive role and be an alternative solution to farmers to promote agricultural land development.